"Casual Sushi" Business Plan - Makhimov, Alisher; Habrmanová, Blanka; Küchler, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This bachelor work is focused on the realization of a business plan in the field of gastronomy. The basis of this work was the opening of a small sushi bar in the shopping centre. Aim of this thesis is following: to create a business plan for opening a sushi point and evaluate its feasibility in money.In terms of overall market introduction, it is necessary to underline the following points: economic growth of Czech economy, large number of competitors, growing demand for qualitative food. The main conclusions of the business plan are: initial investment is 935 312,09 CZK, annual profit is 956 611,78 CZK, payback period is 1,13 years, index of profitability is 3,92, NPV is 2 482 928 CZK and IRR is 94,79 %. The business plan definitely stands for implementation.
Vedoucí práce: Blanka Habrmanová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses